Respiratory infections in the post-COVID-19 era: impact, prevalence, and clinical characteristics of bacterial and viral co-infections - Trifonova, I.; Korsun, N.; Levterova, V.; Pavlova, D.; Simeonovski, I.; Ivanova, M.; Velikov, P.; Voleva, S.; Ivanov, I.; Ivanov, D.; Dakov, T.; Tcherveniakova, T.; et al. (Frontiers in Medicine, 2025)
IntroductionHumans are affected by respiratory infections globally, originating from both bacterial and viral agents. However, the pathogens responsible for respiratory tract infections and the specific effects of viral-viral, viral-bacterial, and bacterial-bacterial co-infections on disease progression and clinical outcomes remain unclear. Тhis study aimed to determine the prevalence, estimate the age burden, and provide clinical characteristics of mono- and co-infections involving various bacterial and viral co-pathogens.MethodsA total of 609 nasopharyngeal specimens were collected from outpatients and hospitalized patients with respiratory symptoms between April and December 2024. The specimens were analyzed using an in-house multiplex real-time polymerase chain reaction method. Six separate primer and probe mixtures were prepared to detect 15 respiratory viruses and 5 common bacterial respiratory pathogens.ResultsThis study, conducted over an 8-month period, found that 65.7% of the patients (400) had at least one respiratory pathogen, with viral infections (49.2%) being more common than bacterial infections (16.5%). Infections were categorized as follows: Viral mono-infections: 217 cases (35.6%); Bacterial-bacterial co-infections: 6 cases (1%); Viral-viral co-infections: 39 cases (6.4%); and Bacterial-viral co-infections: 87 cases (34.3%). Common pathogens causing mono- and co-infections included SARS-CoV-2, rhinovirus, influenza A/B, bocavirus, adenovirus, Streptococcus pneumoniae, and Streptococcus pyogenes. Mixed infections were more common in children aged <5 years (p < 0.05). The disease resulted in a fatal outcome in four patients (1.3%). Notably, one patient with confirmed Streptococcus pneumoniae serotype 11A/D had a fatal outcome. Analysis of age as a factor in infection severity revealed that infants aged 7–11 months and patients aged >65 years with bacterial-viral co-infections had mean saturations of 89.6 ± 10.4% and 90 ± 5%, respectively. Moreover, hospitalized patients aged >65 with viral-viral co-infections exhibited significantly higher C-reactive protein levels (150.8 ± 14.3 mg/L) compared to children aged < 15 (p < 0.05).ConclusionThis study identified SARS-CoV-2, rhinoviruses, adenoviruses, and Streptococcus pneumoniae as key respiratory pathogens associated with mono- and co-infections. Mixed infections with SARS-CoV-2 were associated with progressively worsening symptoms, particularly in patients aged >65 years. This study highlights the need for preventive measures, including vaccination and revaccination of older adults with vaccines covering a broader range of S. pneumoniae serotypes.